2019
DOI: 10.1177/0885328219859830
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable cellulose nanocrystal and tropoelastin-laden hyaluronic acid hydrogels

Abstract: Hyaluronic acid (HA)-based hydrogels have been widely used as cell culture substrates, adhesives and fillers for clinical therapeutics, and drug delivery vehicles, with promising results. Due to the limited mechanical properties, degradation rates, and biological activity of HA, it is important that HA be chemically modified, cross-linked or reinforced with specific components to confer a versatile range of viscoelastic and biophysical cues. Herein, we present a toolbox comprising of a class of in situ cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The small dimensions of CNC also provided greater surface area and interstitial volume, which allowed the hydrogel to retain more water [ 51 ]. While other studies reported reduced swelling with increased CNC concentration [ 43 , 44 , 45 ], it should be emphasized that these studies used modified CNC. CNC oxidation with sodium periodate added a dialdehyde group to its structure, which reacts with the free amine group of gelatin through Schiff base formation [ 43 ].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The small dimensions of CNC also provided greater surface area and interstitial volume, which allowed the hydrogel to retain more water [ 51 ]. While other studies reported reduced swelling with increased CNC concentration [ 43 , 44 , 45 ], it should be emphasized that these studies used modified CNC. CNC oxidation with sodium periodate added a dialdehyde group to its structure, which reacts with the free amine group of gelatin through Schiff base formation [ 43 ].…”
Section: Discussionmentioning
confidence: 95%
“…CNC has no covalent interaction with gelatin unless it is functionalised with aldehyde groups via sodium periodate oxidation [ 43 , 44 ]. CNC could also be modified with diosgenin to allow it to be crosslinked with gelatin via genipin [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…168 Silva et al prepared a composite hyaluronic acid/CNC/tropoelastin hydrogel as a cell growing substrate. 169 The incorporation of CNCs improved the hydrogel's stability against hydrolytic and enzymatic degradation due to the chemical bonding of CNCs and hyaluronic acid. The resulting gels were shown to support and promote cell adhesion, viability and growth, which is indispensable for tissue engineering and regeneration applications.…”
Section: Nc For Tissue Engineeringmentioning
confidence: 99%